2018
DOI: 10.1055/s-0037-1607391
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Severe Asthma

Abstract: Severe therapy-resistant asthma has been defined as "asthma which requires treatment with high dose inhaled corticosteroids (ICSs) plus a second controller (and/or systemic corticosteroids) to prevent it from becoming 'uncontrolled' or which remains 'uncontrolled' despite this therapy". Patients who usually present with 'difficult-to-treat asthma' should first be assessed to determine whether he/she has asthma with the exclusion of other diagnoses and if so, whether the asthma can be classified as severe thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Immune deviation from a T2-high asthma to a T2-low asthma/T1 endotype is characterized by biomarkers of neutrophil recruitment e.g., IL-1alpha, IL-6, IL-8 43 , innate immune response dysregulation e.g., IL-23, TNF alpha, interferon, IL-17 4448 , and includes neutrophilic noneosinophilic asthma 49 . Neutrophilic asthma is significantly increased in smokers with asthma compared to nonsmokers with asthma 50 and in previous smokers with severe asthma compared to never smokers with severe asthma 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune deviation from a T2-high asthma to a T2-low asthma/T1 endotype is characterized by biomarkers of neutrophil recruitment e.g., IL-1alpha, IL-6, IL-8 43 , innate immune response dysregulation e.g., IL-23, TNF alpha, interferon, IL-17 4448 , and includes neutrophilic noneosinophilic asthma 49 . Neutrophilic asthma is significantly increased in smokers with asthma compared to nonsmokers with asthma 50 and in previous smokers with severe asthma compared to never smokers with severe asthma 51 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 is a biomarker of uncontrolled asthma and is associated with increased blood 122 and bronchoalveolar lavage (BAL) neutrophils 123 , oral/parenteral glucocorticoid unresponsiveness 122 , and reduced pulmonary function 122,123 . Endotypes of treatment resistant severe asthma include neutrophilic T2-low asthma 43,49,124 e.g., T2-low/Th17-low 43 , T1/Th17 125,126 which are associated with subclinical bronchial infection, increased IL-8 43 , lower airway dysbiosis 127 , and systemic inflammation 128 .…”
Section: Discussionmentioning
confidence: 99%
“…Many of the patients in ProAR recognized as having uncontrolled asthma may not truly have SA, as there may be modifiable factors worsening the disease (31). One of these factors is the presence of other chronic morbidities in addition to asthma (32,33), of which there was a high incidence among the individuals with ERS/ATS 2014 SA, corroborating the findings of Hekking (34).…”
Section: Discussionmentioning
confidence: 52%
“…This study showed a higher proportion of patient (78%) that had at least one asthma exacerbation in the previous year. Indeed, the literature also points to a high number of SA patients experiencing exacerbations in other cohorts, with 41% to 83% of SA patients reporting at least one exacerbation in the last year in these studies (22)(23)(24)28,32). Although the frequency reported varied among studies, probably because of methodological differences and definition of exacerbations, all studies report that these patients are experiencing a high frequency of exacerbations, highlighting what is still an unmet need for these patients.…”
Section: Discussionmentioning
confidence: 90%
“…A thorough investigation of all of the factors associated with difficult-to-control asthma in every asthma patient is unnecessary. 31 However, in cases of difficult-to-control asthma, which affects 17.4% of all adult asthma patients and 74.1% of those in treatment classified as GINA step 4 or 5, 32 a systematic investigation must be performed to identify, minimize, or eliminate comorbidities (such as gastroesophageal reflux, obesity, vocal cord dysfunction, chronic rhinosinusitis, nasal polyposis, anxiety, depression, sleep apnea, COPD, allergic bronchopulmonary aspergillosis, and bronchiectasis) and to avoid asthma being caused or worsened by occupational exposure, among other things that can impair the disease control.…”
Section: Introductionmentioning
confidence: 99%